2020
DOI: 10.1186/s13054-020-03115-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dexmedetomidine on vasopressor requirements in patients with septic shock: a subgroup analysis of the Sedation Practice in Intensive Care Evaluation [SPICE III] Trial

Abstract: Background: Septic shock is associated with decreased vasopressor responsiveness. Experimental data suggest that central alpha2-agonists like dexmedetomidine (DEX) increase vasopressor responsiveness and reduce catecholamine requirements in septic shock. However, DEX may also cause hypotension and bradycardia. Thus, it remains unclear whether DEX is hemodynamically safe or helpful in this setting. Methods: In this post hoc subgroup analysis of the Sedation Practice in Intensive Care Evaluation (SPICE III) tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 32 publications
1
68
0
2
Order By: Relevance
“…This hypothesis also suggests that the more the α1-receptors are desensitized by high concentrations of endogenous catecholamines (e.g., in refractory septic shock), the larger the expected improved responsiveness to vasopressors. In recent studies and subgroup analyses, dexmedetomidine appeared to be associated with lower vasopressor requirements to maintain the same MAP target in septic shock [ 101 , 102 ].…”
Section: Therapeutic Interventions To Modulate the Ans In Septic Shockmentioning
confidence: 99%
“…This hypothesis also suggests that the more the α1-receptors are desensitized by high concentrations of endogenous catecholamines (e.g., in refractory septic shock), the larger the expected improved responsiveness to vasopressors. In recent studies and subgroup analyses, dexmedetomidine appeared to be associated with lower vasopressor requirements to maintain the same MAP target in septic shock [ 101 , 102 ].…”
Section: Therapeutic Interventions To Modulate the Ans In Septic Shockmentioning
confidence: 99%
“…In this regard, a recent post hoc subgroup analysis of patients with septic shock ( N = 83) included in the SPICE III trial reported similar vasopressor requirements in the first 48 h in patients. However, on multivariable adjusted analysis (for admission diagnosis, baseline noradrenaline equivalents/MAP ratio, continuous renal replacement therapy, age, hydrocortisone treatment, and liver cirrhosis), vasopressor requirements to maintain target MAP were significantly lower in the dexmedetomidine than in the usual care group (ratio of difference in geometric means 1.44 [1.07, 1.95]) (Cioccari et al, 2020).…”
Section: Organ Dysfunction Arising From Sepsismentioning
confidence: 99%
“…It has sedative, anxiolytic, and analgesic properties with minimal respiratory depression. 75 While the main side effects of dexmedetomidine are hypotension and bradycardia in vasopressor dependent patients, it is well tolerated and shown to reduce vasopressor requirements in septic patients 33,76 and improve outcomes after cardiac surgery. 77 The commonest use of dexmedetomidine in clinical practice is in the management of delirium and agitation.…”
Section: Optimal Sedation Managementmentioning
confidence: 99%